The Construction of Narratives Regarding Accusations of Wahabism and Anti-Pancasila Against PKS in the Mass Media - Henry Sianipar; Rahmat Saleh; Andi Faisal Bakti (Green Publisher Indonesia, 2026)
This study examines the narratives constructed by mass media regarding accusations of Wahabism and anti-Pancasila associated with the Prosperous Justice Party (PKS) in Indonesia. Utilizing a critical paradigm, the research analyzes the impact of media coverage on public opinion and the ideological implications for PKS. Through qualitative methods—including in-depth interviews with four key informants (PKS Secretary General H. Muhammad Kholid, Head of PKS DPP Organization Bureau Sunarto, media observer Andre Bachtiar, and political researcher Revan Fauzano from Constra Indonesia) and critical discourse analysis of online media content from 2019–2024—this study reveals systematic patterns in media discourse that contribute to the stigmatization of PKS. The findings highlight the role of disinformation in shaping political narratives and uncover a disconnect between media representations and PKS's actual ideology, which upholds Pancasila as its foundational principle. The results emphasize the need for improved journalistic practices and media literacy to counteract sensationalism and misinformation in political communication. This study contributes to political communication literature by providing empirical validation of Aeron Davis's theory on structural crisis in digital-age political communication, demonstrating how media political economy, attention economy, and mediatization processes interact to produce systematic disinformation campaigns against political actors. Recommendations include structural media industry reforms addressing business model crises, regulatory frameworks emphasizing transparency and accountability rather than censorship, multi-stakeholder dialogue forums, and comprehensive public media literacy programs integrated with community institutions.